Physician characteristics associated with the referral from general practitioners to dental surgeons and proposal for a referral letter template endorsed by dental surgeons in France: a nationwide cross-sectional survey-based study - Matthias Lamauviniere; Jan Chrusciel; Cassandre Finot; Adrien Basset; Maximillien Graftieaux; Aline Ohl-Hurtaud; Stéphane Sanchez (BMC Primary Care)
Abstract Background Interprofessional relationships between general practitioners (GPs) and dental surgeons with a doctorate in dental surgery are essential for the optimal management of the oral health of patients. The objectives of this study were to describe the factors associated with the referral of patients from GPs to dental surgeons in France, and to improve referral practices by establishing a standardized set of items to be included in a referral letter. Methods A nationwide, observational, survey-based, cross-sectional study was conducted from 9 February 2023 to 6 April 2023. Two 13-item questionnaires were sent to GPs and dental surgeons. Data on practitioner characteristics, frequency, and perceived usefulness of medical correspondence between the two healthcare professionals were collected. Candidate items selected by expert medical opinion for a standardized referral letter template were appraised by the responding oral surgeons. Results A group of 245 dental surgeons (mean age: 38.2 ± 11.1 years, 64.5% female) and 235 GPs (mean age: 36.8 ± 9.8 years, 71.9% female) participated in this study. Medical correspondence between GPs and dental surgeons was reported to be insufficient by most dental surgeons (91.4%). Dental surgeons agreed that GP correspondence could decrease the occurrence of adverse events linked with dental care (mean score: 7.36 ± 2.4, for a maximum of 10). Only 20% of GPs indicated that they had regular communication with dental surgeons. The physician characteristics under study were not statistically associated with initiating referrals. The items most frequently selected by dental surgeons for inclusion in a template referral letter were the presence of diabetes (99.6%), of immunosuppression (98.8%), and medication by anticoagulant or antiplatelet agents (98.3%). Conclusions Despite known links between oral and general health, most healthcare professionals did not engage in correspondence or referrals with the other specialty. Standardized referral letters could include the list of items for which interest was confirmed by dental surgeons (including presence of diabetes, immunosuppressants and anticoagulants or antiplatelet agents).